Carburizing coating agent and method for manufacturing steel using the same

CN123022832APending Publication Date: 2026-10-30NIPPON STEEL CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580024205.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-05
Filing Date
2025-04-04
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0019]本实施方式的渗碳涂布剂能够使用氧化性气氛的热处理炉进行渗碳处理。本实施方式的钢材的制造方法能够制造表层被渗碳的钢材。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The carburizing coating agent of the embodiment of the present disclosure contains a glass frit and a carbon powder. The glass frit contains SiO2: 20.0 to 40.0%, Al2O3: 10.0 to 30.0%, B2O3: 9.0 to 40.0%, Na2O: 0 to 30.0%, K2O: 0 to 5.0%, CaO: 0 to 7.0%, and MgO: 0 to 5.0% in terms of mass% when converted into oxides, and the ratio of the mass (g) of the carbon powder in the carburizing coating agent to the mass (g) of the glass frit is 0.10 to 0.49.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a carburizing coating agent and a method for manufacturing steel using the same. Background Technology

[0002] In steels requiring fatigue strength or wear resistance, a carburizing process is sometimes performed, where carbon (C) is infiltrated into the surface of the steel, followed by quenching to harden the surface. Gas carburizing is the primary method used in this process.

[0003] Gas carburizing involves heating and holding steel in an atmosphere containing carburizing gases such as natural gas, propane, or butane to achieve the carburizing process. In gas carburizing, the carburizing gas needs to be in contact with the steel surface at a high concentration. Therefore, equipment is used to fill the furnace with carburizing gas. If carburizing can be performed in a heat treatment furnace heated in an oxidizing atmosphere without using such specialized gas carburizing equipment, manufacturing costs can be reduced.

[0004] Therefore, as an alternative to the above-mentioned gas carburizing, Japanese Patent Application Publication No. 2000-119838 (Patent Document 1), Japanese Patent Application Publication No. 2001-115249 (Patent Document 2), and Japanese Patent Application Publication No. 2016-223011 (Patent Document 3) have proposed a method for carburizing by applying a specific coating to the surface of steel.

[0005] In the carburizing methods of Patent Documents 1 and 2, a coating-type carburizing composition is used. The coating-type carburizing composition contains an olefin-based polymer resin and an aqueous medium. Furthermore, the coating-type carburizing composition contains: charcoal powder as a carburizing agent, in an amount of 10 to 100 parts by weight relative to 100 parts by weight of the resin; and sodium carbonate as a carburizing accelerator, in an amount of 5 to 80 parts by weight relative to 100 parts by weight of the resin. In the carburizing methods of Patent Documents 1 and 2, the above-mentioned coating-type carburizing composition is applied to the carburized portion of the steel and dried to form a film. Then, the steel is heated in a heat treatment furnace under an oxidizing atmosphere to perform the carburizing treatment.

[0006] In the carburizing method of Patent Document 3, a surface treatment agent comprising a sodium silicate solution and one or more metal compounds selected from the group consisting of metal oxides and carbonates is prepared. In this carburizing method, after the above-mentioned surface treatment agent is applied to the surface of the steel, carburizing is performed in a heat treatment furnace with an oxidizing atmosphere.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2000-119838

[0010] Patent Document 2: Japanese Patent Application Publication No. 2001-115249

[0011] Patent Document 3: Japanese Patent Application Publication No. 2016-223011 Summary of the Invention

[0012] The problem the invention aims to solve

[0013] However, carburizing can also be performed in a heat treatment furnace in an oxidizing atmosphere by means other than those described in Patent Documents 1 to 3.

[0014] The purpose of this disclosure is to provide a carburizing coating agent capable of carburizing in a heat treatment furnace with an oxidizing atmosphere, and a method for manufacturing steel using the carburizing coating agent.

[0015] Solution for solving the problem

[0016] The carburizing coating agent disclosed herein contains glass frit and carbon powder. The glass frit contains, by mass percent (converted to oxides): SiO2: 20.0–40.0%, Al2O3: 10.0–30.0%, B2O3: 9.0–40.0%, Na2O: 0–30.0%, K2O: 0–5.0%, CaO: 0–7.0%, and MgO: 0–5.0%. The mass ratio (g) of carbon powder to the mass (g) of glass frit in the carburizing coating agent is 0.10–0.49.

[0017] The steel manufacturing method disclosed herein includes the following steps: applying the carburizing coating agent disclosed herein to the surface of the steel; and heating the steel coated with the carburizing coating agent at 950 to 1300°C.

[0018] The effects of the invention

[0019] The carburizing coating agent of this embodiment can be carburized using a heat treatment furnace with an oxidizing atmosphere. The steel manufacturing method of this embodiment can produce steel with a carburized surface. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the EPMA spectrum used to illustrate the method for determining the C concentration ratio ΔC in the embodiments. Detailed Implementation

[0021] The inventors have studied a carburizing process using a heat treatment furnace with an oxidizing atmosphere. They first investigated the principle of forming a carburized layer on the surface of steel through gas carburizing.

[0022] In gas carburizing, the carburized layer is formed according to the following principle: Steel is heated in a temperature range of 950–1300°C. A carburizing gas, such as carbon monoxide (CO), comes into contact with the surface of the steel in this temperature range. At this time, the carbon in the carburizing gas penetrates and diffuses from the steel surface into the steel's surface layer. As a result, a carburized layer is formed on the surface of the steel. In the above principle, the carburizing gas functions as a carbon supply source, forming a carburized layer on the steel surface.

[0023] However, in a heat treatment furnace with an oxidizing atmosphere, it is difficult to fill the atmosphere with carburizing gas. Therefore, the inventors have investigated using a new carbon supply source to perform carburizing treatment instead of carburizing gas. Here, the inventors considered using carbon powder as the carbon supply source. The carbon powder reacts with oxygen in the oxidizing atmosphere to generate CO gas. If this CO gas comes into contact with the surface of the steel, it is possible to form a carburized layer on the surface of the steel.

[0024] However, even if CO gas is generated from carbon powder, a carburized layer cannot be fully formed if the CO gas does not remain near the surface of the steel.

[0025] Here, the inventors believe that if a coating can be formed on the steel surface to suppress the diffusion of CO gas generated by carbon powder coated on the steel surface into the furnace, carburizing can be performed even in a heat treatment furnace with an oxidizing atmosphere. Specifically, a carburizing coating agent is used, which contains a composition that vitrifies on the steel surface in the temperature range of 950 to 1300°C, and carbon powder. In this case, a vitrified coating containing carbon powder is formed on the steel surface in the high-temperature range. If this coating can seal the CO gas generated by the carbon powder between the steel surface and the coating, the CO gas remains on the steel surface. As a result, a carburized layer can be formed on the steel surface even in a heat treatment furnace with an oxidizing atmosphere. In the following description, the above-mentioned coating that suppresses the diffusion of CO gas and remains on the steel surface is referred to as a "CO gas diffusion suppression film".

[0026] Based on the above investigation, the inventors studied the composition of a carburizing coating agent capable of forming a CO gas dispersion-inhibiting film in a high-temperature region. As a result, the inventors concluded that using a glass frit as the composition for vitrification in a high-temperature region is effective. Therefore, the inventors further investigated the composition of the glass frit.

[0027] As a component of the glass frit, by adjusting the contents of SiO2 and Al2O3 (components that increase the softening point) and B2O3, Na2O, K2O, CaO, and MgO (components that decrease the softening point), a CO gas emission suppression film that fully wets and spreads on the steel surface and can fully cover the steel surface can be formed in the temperature range of 950–1300°C. Therefore, the inventors adjusted the contents of the above-mentioned components and investigated the relationship between the composition of the glass frit and the carburizing effect on the steel surface at high temperatures. The results showed that if the glass frit contains, by mass percent (converted to oxides), SiO2: 20.0–40.0%, Al2O3: 10.0–30.0%, B2O3: 9.0–40.0%, Na2O: 0–30.0%, K2O: 0–5.0%, CaO: 0–7.0%, and MgO: 0–5.0%, then when steel is heated in the temperature range of 950–1300°C, it may be possible to carburize the surface of the steel.

[0028] However, even when using a carburizing coating agent containing the aforementioned glass frit and carbon powder, it is sometimes impossible to fully form a carburized layer on the surface of the steel. The investigation revealed that the reason for the insufficient formation of the carburized layer lies in the mixing ratio of the glass frit and carbon powder. This will be explained below.

[0029] In carburizing coating agents, if the mass (g) of carbon powder is too small relative to the mass (g) of glass frit, CO gas, which is a carburizing gas, cannot be sufficiently generated. In this case, a sufficiently carburized layer cannot be formed on the surface of the steel. On the other hand, if the mass of carbon powder is too large relative to the mass of glass frit, a CO gas emission suppression film cannot be stably formed in high-temperature regions. Therefore, in the temperature range of 950–1300°C, the CO gas emission suppression film will crack or a portion of the film will peel off. As a result, CO gas will escape into the heat treatment furnace.

[0030] Therefore, the inventors believe that there exists an appropriate mixing ratio between the mass (g) of the glass frit and the mass (g) of the carbon powder. Through repeated studies, the inventors discovered that in a carburizing coating agent containing the above-described glass frit, if the mass (g) of the carbon powder relative to the mass (g) of the glass frit is 0.10 to 0.49, sufficient CO gas can be generated from the carbon powder, which serves as a carbon supply source, thereby stably forming a CO gas dispersion suppression film in the high-temperature region.

[0031] Based on the above insights, the main points of the carburizing coating agent and the method for manufacturing steel using the same in the embodiments of this disclosure are as follows.

[0032] The first type of carburizing coating agent contains glass frit and carbon powder. The glass frit contains, by mass percent (converted to oxides): SiO2: 20.0–40.0%, Al2O3: 10.0–30.0%, B2O3: 9.0–40.0%, Na2O: 0–30.0%, K2O: 0–5.0%, CaO: 0–7.0%, and MgO: 0–5.0%. The mass ratio (g) of carbon powder to the mass (g) of glass frit in the carburizing coating agent is 0.10–0.49.

[0033] The steel manufacturing method of this embodiment includes the following steps: applying the carburizing coating agent described in the first embodiment to the surface of the steel; and heating the steel coated with the carburizing coating agent at 950 to 1300°C.

[0034] The following describes the carburizing coating agent of this embodiment and the manufacturing method of steel using the carburizing coating agent.

[0035] [About carburizing coating agents]

[0036] The carburizing coating agent of this embodiment contains glass frit and carbon powder. The glass frit and carbon powder will be described below.

[0037] [Regarding glass materials]

[0038] Glass frit refers to glass produced by melting glass raw materials, solidifying them, and then pulverizing them. Glass frit can be granular or sheet-like. The carburizing coating agent of this embodiment contains the following glass frit, expressed as a percentage by mass of oxides: SiO2: 20.0–40.0%, Al2O3: 10.0–30.0%, B2O3: 9.0–40.0%, Na2O: 0–30.0%, K2O: 0–5.0%, CaO: 0–7.0%, and MgO: 0–5.0%. The composition of each component will be described below.

[0039] SiO2: 20.0%–40.0%

[0040] Silica (SiO2), along with other components, forms a CO gas dispersion suppression film on the steel surface in a heat treatment furnace with an oxidizing atmosphere at temperatures ranging from 950 to 1300°C. SiO2 serves as the matrix for this film. The CO gas dispersion suppression film allows oxygen to permeate. Therefore, oxygen from outside the CO gas dispersion suppression film invades the interior of the film, i.e., between the film and the steel surface. In this case, the oxygen reacts with carbon on the steel surface to generate CO gas. On the other hand, the generated CO gas does not easily permeate through the CO gas dispersion suppression film. Therefore, CO gas does not easily disperse from the film into the external oxidizing atmosphere. Thus, the CO gas generated by the carbon powder, which serves as the carbon supply source, remains between the film and the steel surface. As a result, CO-based carburizing is promoted. If the SiO2 content is less than 20.0%, the above effect cannot be fully obtained.

[0041] On the other hand, if the SiO2 content exceeds 40.0%, the softening point of the carburizing agent becomes too high. In this case, the carburizing agent struggles to wet and spread in the temperature range of 950–1300°C. Consequently, the CO gas dispersion-inhibiting film formed by the carburizing agent cannot adequately cover the steel surface. As a result, the steel surface is not sufficiently carburized. Therefore, the SiO2 content should be between 20.0% and 40.0%.

[0042] The preferred lower limit for SiO2 content is 22.0%, and more preferably 25.0%.

[0043] The preferred upper limit for SiO2 content is 37.0%, and more preferably 35.0%.

[0044] Al2O3: 10.0–30.0%

[0045] Similar to SiO2, alumina (Al2O3), along with other components, forms a CO gas emission suppression film on the steel surface in the temperature range of 950–1300°C within an oxidizing atmosphere heat treatment furnace. Al2O3, together with SiO2 and B2O3, forms the matrix of the CO gas emission suppression film. Al2O3 further increases the softening point of the glass frit. Therefore, in the aforementioned temperature range, it inhibits the dripping of carburizing agent from the steel surface, making it easier for the carburizing agent to remain on the steel surface. Consequently, in the aforementioned temperature range, the CO gas emission suppression film formed by the carburizing agent can sufficiently cover the steel surface, promoting CO gas-based carburizing. If the Al2O3 content is less than 10.0%, the above effects cannot be fully obtained.

[0046] On the other hand, if the Al2O3 content exceeds 30.0%, the SiO2 content decreases relative to the Al2O3 content. In this case, the softening point of the glass frit becomes lower. As a result, in high-temperature regions, the carburizing agent is more likely to drip off the steel surface. Therefore, the Al2O3 content is typically between 10.0% and 30.0%.

[0047] The preferred lower limit for Al2O3 content is 12.0%, more preferably 14.0%, and even more preferably 18.0%.

[0048] The preferred upper limit for Al2O3 content is 28.0%, more preferably 25.0%, and even more preferably 23.0%.

[0049] B2O3: 9.0–40.0%

[0050] Like SiO2, boron oxide (B2O3), along with other components, forms a CO gas emission suppression film on the steel surface in the temperature range of 950–1300°C within an oxidizing atmosphere heat treatment furnace. B2O3, together with SiO2 and Al2O3, forms the matrix of this CO gas emission suppression film. B2O3 further lowers the softening point of the carburizing agent. Therefore, in the aforementioned temperature range, the carburizing agent readily wets and spreads, resulting in a CO gas emission suppression film formed by the carburizing agent that adequately covers the steel surface. If the B2O3 content is less than 9.0%, the aforementioned effect cannot be fully achieved.

[0051] On the other hand, if the B2O3 content exceeds 40.0%, the softening point of the carburizing agent becomes too low. In this case, within the aforementioned temperature range, the carburizing agent easily drips from the steel surface. As a result, the steel surface is not sufficiently carburized. Therefore, the B2O3 content should be between 9.0% and 40.0%.

[0052] The preferred lower limit for the B2O3 content is 9.5%, further preferably 10.0%, further preferably 20.0%, and further preferably 25.0%.

[0053] The preferred upper limit for the B2O3 content is 37.0%, more preferably 35.0%, and even more preferably 33.0%.

[0054] Na2O: 0~30.0%

[0055] It may also be free of sodium oxide (Na2O). That is, Na2O can be any component, and the Na2O content can be 0%.

[0056] When present in the presence of Na₂O, i.e., when the Na₂O content exceeds 0%, Na₂O lowers the softening point of the glass frit. Therefore, in the temperature range of 950–1300°C, the fluidity of the carburizing coating agent improves. As a result, in this temperature range, the CO gas emission suppression film can adequately cover the steel surface.

[0057] Compared to other alkaline components (K2O, CaO, and MgO), Na2O is less likely to react with oxide scale, which is mainly composed of Fe oxides. Therefore, when carbon steel (hereinafter also referred to as carbon steel) is heated in the temperature range of 950–1300°C, the destruction of oxide scale caused by reaction with oxide scale can sometimes be suppressed. As a result, in the high-temperature region, decarburization that accompanies the destruction of oxide scale can be suppressed. This effect is achieved to some extent even with a small amount of Na2O.

[0058] However, if the Na₂O content exceeds 30.0%, the softening point of the glass frit is excessively lowered. In this case, within the aforementioned temperature range, the carburizing agent drips from the steel surface. As a result, the CO gas emission suppression film cannot adequately cover the steel surface, and the steel surface is not sufficiently carburized. Therefore, the Na₂O content should be between 0% and 30.0%.

[0059] The preferred lower limit for Na2O content is 0.1%, more preferably 0.5%, more preferably 3.0%, more preferably 5.0%, more preferably 6.0%, and more preferably 10.0%.

[0060] The preferred upper limit for Na2O content is 28.0%, more preferably 26.0%, more preferably 25.0%, more preferably 23.0%, more preferably 20.0%, and more preferably 19.0%.

[0061] K2O: 0~5.0%

[0062] It may also be free of potassium oxide (K2O). That is, K2O can be any component, and the K2O content can be 0%.

[0063] When K2O is present, i.e., the K2O content exceeds 0%, K2O lowers the softening point of the glass frit. Therefore, in the temperature range of 950–1300°C, the fluidity of the carburizing coating agent improves. As a result, in this temperature range, the CO gas emission suppression film can adequately cover the steel surface.

[0064] However, compared to Na2O, K2O reacts more readily with oxide scale, which is mainly composed of Fe oxides. Therefore, when carbon steel is heated in the temperature range of 950–1300°C, K2O reacts with the oxide scale, easily damaging it. For these reasons, a low K2O content is preferred in the carburizing coating agent of this embodiment. Therefore, the K2O content is 0–5.0%.

[0065] The preferred lower limit for K2O content is 0.1%, more preferably 0.5%, and even more preferably 1.0%.

[0066] The preferred upper limit for K2O content is 4.0%, further preferably 3.0%, and even more preferably 2.0%.

[0067] CaO: 0–7.0%

[0068] It may also be free of calcium oxide (CaO). That is, CaO can be any component, and the CaO content can be 0%.

[0069] When CaO is present, i.e., the CaO content exceeds 0%, CaO lowers the softening point of the glass frit. Therefore, the fluidity of the carburizing coating agent increases in the temperature range of 950–1300°C. As a result, in this temperature range, the CO gas emission suppression film can adequately cover the steel surface. However, compared to Na₂O, CaO reacts more readily with oxide scale, which is primarily composed of Fe oxides. Therefore, when the aforementioned carbon steel is heated at high temperatures, CaO reacts with the oxide scale, easily destroying it.

[0070] CaO further promotes the diffusion of oxygen into CO gas, inhibiting the permeation of the coating. As mentioned above, the carbon powder in the carburizing agent reacts with oxygen to generate CO gas. However, if excessive oxygen in the oxidizing atmosphere of the furnace permeates through the CO gas diffusion inhibition film during high-temperature heating, the generated CO gas further reacts with oxygen to become CO2 gas. CO2 gas does not contribute to carburization on the steel surface; therefore, if CO gas decreases due to CO2 gas generation, the steel surface will not be sufficiently carburized. If the CaO content exceeds 7.0%, excessive CO2 gas is generated. Therefore, the CaO content should be between 0% and 7.0%.

[0071] The preferred lower limit for CaO content is 0.1%, more preferably 0.3%, more preferably 1.0%, more preferably 2.0%, and more preferably 3.0%.

[0072] The preferred upper limit for CaO content is 6.0%, more preferably 5.0%, and even more preferably 4.0%.

[0073] MgO: 0–5.0%

[0074] It may also be free of magnesium oxide (MgO). That is, MgO can be any component, and the MgO content can be 0%.

[0075] In its presence, MgO lowers the softening point of the glass frit. Therefore, during heating in the temperature range of 950–1300°C, the carburizing agent wets and spreads, effectively covering the steel surface. Even a small amount of MgO is sufficient to achieve this effect to some extent.

[0076] However, while MgO is not as reactive as K₂O and CaO, it reacts more readily with oxide scale, which is primarily composed of Fe oxides, compared to Na₂O. Therefore, if the MgO content exceeds 5.0%, it will react with the oxide scale during high-temperature heating, easily destroying it. Thus, the MgO content should be between 0% and 5.0%.

[0077] The preferred lower limit for MgO content is 0.1%, and more preferably 0.5%.

[0078] The preferred upper limit for MgO content is 4.5%, more preferably 4.0%, more preferably 3.0%, more preferably 2.0%, and more preferably 1.0%.

[0079] The glass frit of this embodiment contains the above-described components. It should be noted that the glass frit may contain 0 to 1.0% impurities (converted to oxides by mass%) as the balance other than the above-described components. These impurities may be introduced during the industrial manufacture of the glass frit from inorganic materials used as raw materials or from the manufacturing environment. Examples of such impurities include Fe₂O₃, B₂O₃, ZrO₂, TiO₂, Sb₂O₃, SrO, BaO, ZnO, PbO, Li₂O, and P₂O₅.

[0080] [Methods for Compositional Analysis of Glass Components]

[0081] The composition of the glass frit was analyzed using the following method. The composition of the glass frit was obtained by performing high-frequency inductively coupled plasma (ICP) analysis on the dried glass frit. Specifically, the contents of elements such as Si, Al, B, Na, K, Ca, and Mg were determined through ICP analysis. Assuming that all elements form oxides, the oxide contents of each element were calculated from the element contents obtained through ICP analysis. The total content of all oxides obtained through the conversion was set as 100%, and the content of each oxide was taken as the content (mass %) of each component in the glass frit.

[0082] [About carbon powder]

[0083] The carburizing coating agent also contains carbon powder. Carbon powder is a powder composed of carbon. For example, the carbon powder may consist of one or more particles selected from the group consisting of graphite powder, carbon black powder, charcoal powder, bamboo charcoal powder, and coke powder. Preferred carbon powder is graphite powder.

[0084] As described above, in a temperature range of 950–1300°C under an oxidizing atmosphere, the carburizing agent forms a CO gas emission suppression film on the steel surface. At this time, the carbon in the carbon powder is contained within the CO gas emission suppression film, functioning as a carbon supply source in the aforementioned temperature range. Specifically, the carbon in the CO gas emission suppression film reacts with oxygen permeating through the film to generate CO gas. While the CO gas emission suppression film is permeable to oxygen, it is not easily permeable to CO gas. Therefore, the generated CO gas remains between the CO gas emission suppression film and the steel surface. Thus, through contact between CO gas and the steel surface, the steel surface undergoes carburization.

[0085] [Regarding the carbon powder ratio RA]

[0086] The ratio of the mass (g) of carbon powder to the mass (g) of glass frit in a carburizing coating agent containing carbon powder is defined as the "carbon powder ratio RA". In the carburizing coating agent of this embodiment, the carbon powder ratio RA is 0.10 to 0.49.

[0087] Here, the ratio of the mass of carbon powder (g) to the mass of glass frit (g) refers to the ratio of the mass of carbon powder (g) in its dry state to the mass of glass frit (g) in its dry state.

[0088] If the carbon powder ratio RA is less than 0.10, the carbon supply source is insufficient. In this case, at the aforementioned temperature range, the carbon in the CO gas emission suppression film reacts with oxygen permeating from the outside of the film, failing to generate a sufficient amount of CO gas. Therefore, at the aforementioned temperature range, the steel surface is not sufficiently carburized.

[0089] On the other hand, if the carbon powder ratio (RA) exceeds 0.49, there is an excessive carbon supply. In this case, a stable CO gas dispersion suppression film cannot be formed in the aforementioned temperature range. Specifically, in this temperature range, the CO gas dispersion suppression film will crack, or a portion of the film will peel off. Consequently, the CO gas formed between the CO gas dispersion suppression film and the steel surface will diffuse to the outside of the film. As a result, the steel surface is not sufficiently carburized.

[0090] If the carbon powder ratio RA is 0.10–0.49, the carbon supply source in the CO gas dispersion suppression film is of an appropriate amount. Therefore, in the aforementioned temperature range, sufficient CO gas can be generated for carburizing, and the CO gas dispersion suppression film stably covers the steel surface. Consequently, the steel surface is sufficiently carburized.

[0091] The preferred lower limit for the carbon powder ratio RA is 0.11, more preferably 0.12, more preferably 0.13, more preferably 0.14, and more preferably 0.15.

[0092] The preferred upper limit for the carbon powder ratio RA is 0.47, more preferably 0.45, more preferably 0.40, more preferably 0.38, and more preferably 0.36.

[0093] [Method for determining the carbon powder ratio (RA)]

[0094] The carbon powder ratio RA in the carburizing coating agent is determined by the following method.

[0095] The mass of the carburizing coating agent, which changes due to heat, is determined using a thermogravimetric (TG) apparatus. There is no particular limitation on the mass of the carburizing coating agent; for example, it can be 1 g.

[0096] Specifically, the carburizing coating agent is heated from room temperature (25°C) to 100°C and maintained at 100°C. The moisture contained in the carburizing coating agent evaporates, and the mass X0 of the carburizing coating agent is measured after 30 seconds while maintaining a constant mass. The carburizing coating agent after mass measurement is then heated to 600°C and maintained at 600°C. This oxidizes the carbon powder in the carburizing coating agent, removing the carbon powder from the carburizing coating agent. After removing the carbon powder contained in the carburizing coating agent, the mass X1 of the carburizing coating agent is measured after 30 seconds while maintaining a constant mass. Mass X1 corresponds to the mass of the glass frit. Therefore, mass X0 - mass X1 corresponds to the mass of the carbon powder.

[0097] Using the obtained masses X0 and X1, the carbon powder ratio RA is calculated using the following formula.

[0098] Carbon powder ratio RA=(X0-X1) / X1

[0099] [Effects of the carburizing coating agent in this embodiment]

[0100] The carburizing coating agent of this embodiment contains glass frit and carbon powder. When the steel coated with the carburizing coating agent of this embodiment is heated to 950-1300°C, the carburizing coating agent wets and spreads on the surface of the steel, forming a CO gas emission suppression film.

[0101] The carbon powder contained in the CO gas emission suppression film functions as a carbon supply source in the aforementioned temperature range. Specifically, the carbon powder in the CO gas emission suppression film reacts with oxygen passing through the film to generate CO gas. The CO gas emission suppression film retains the CO gas between the coating agent and the steel surface, inhibiting the emission of CO gas into the oxidizing atmosphere. As a result, the CO gas comes into contact with the steel surface, thereby performing a carburizing treatment on the steel surface.

[0102] [Regarding components other than glass frit and carbon powder in carburizing coating agents]

[0103] In addition to glass frit and carbon powder, the carburizing coating agent of this embodiment may further contain one or more components selected from the group consisting of water, suspending agents, and dispersants. It may also omit these components. Water, suspending agents, and dispersants will be described below.

[0104] [water]

[0105] When the carburizing coating agent is prepared as a slurry, it may contain water, for example. In the slurry-like carburizing coating agent, the preferred water content is, for example, 70 to 100 parts by weight relative to 100 parts by weight of glass frit. If the water content is too low or too high, it will be difficult to apply the carburizing coating agent to the steel surface. By adjusting the water content, the viscosity of the slurry-like carburizing coating agent can be adjusted to a level that allows it to be applied to the steel surface at room temperature.

[0106] [Suspension agent]

[0107] The suspending agent thoroughly disperses the glass frit in the solution (water). The suspending agent may contain, for example, burr clay and bentonite and / or sepiolite. In this embodiment, when the carburizing coating agent contains burr clay and bentonite and / or sepiolite, the carburizing coating agent is less likely to drip from the steel surface. Furthermore, when the carburizing coating agent dries and solidifies, it is less likely to peel off from the steel surface.

[0108] Frog-like clay contains kaolinite-like clay and multiple quartz particles. Specifically, frog-like clay contains kaolinite, halloysite, and quartz.

[0109] Frog-eye clay improves the sag resistance of slurry-like carburizing coatings. Slurry-like carburizing coatings containing frog-eye clay are less prone to dripping when applied to steel surfaces at room temperature. Therefore, if frog-eye clay is present, the carburizing coating can easily cover the entire surface of the steel at room temperature.

[0110] When the carburizing coating agent contains croton clay, the preferred content of croton clay in the carburizing coating agent is 4 parts by mass or more, relative to 100 parts by mass of glass frit. In this case, the carburizing coating agent is less likely to drip from the steel surface. A further preferred content of croton clay is 5 parts by mass or more, and even more preferably 6 parts by mass or more. On the other hand, the upper limit of the preferred content of croton clay is 30 parts by mass. In this case, the glass frit in the carburizing coating agent is sufficiently dispersed on the surface of the steel. Therefore, in high-temperature regions, a CO gas emission suppression film is formed more fully.

[0111] Bentonite is a clay with montmorillonite as its main component. Bentonite may also contain silicate minerals such as quartz and opal, silicate minerals such as feldspar and zeolite, carbonate minerals such as dolomite, sulfate minerals, sulfide minerals such as pyrite, etc.

[0112] Sepiolite is a hydrous magnesium silicate, for example, composed of the chemical formula Mg8Si. 12 O 30 It is represented by (OH)4(OH2)4·8H2O.

[0113] Both bentonite and sepiolite inhibit the peeling of carburizing coating agents. Specifically, the carburizing coating agent is applied to the steel surface at room temperature. Then, it is solidified by heating or drying. When the carburizing coating agent contains bentonite and / or sepiolite, the bentonite and sepiolite inhibit the peeling of the solidified carburizing coating agent from the steel surface. Carburizing coating agents containing bentonite and / or sepiolite are not easily peeled from the steel surface even under external force. The carburizing coating agent may contain one or more of bentonite and sepiolite.

[0114] Relative to 100 parts by weight of glass, the preferred content of bentonite and / or sepiolite is 4 parts by weight or more. In this case, the peel resistance of the carburizing coating agent is further improved. A further preferred content of bentonite and / or sepiolite is 5 parts by weight or more.

[0115] Relative to 100 parts by weight of glass, the preferred total content of bentonite and sepiolite is less than 9 parts by weight. In this case, the glass is sufficiently dispersed in the carburizing coating agent. More preferably, the total content of bentonite and sepiolite is less than 8 parts by weight.

[0116] The suspending agent may contain other clay types besides the aforementioned frog clay, bentonite, and sepiolite. These clay types may contain, for example, iron oxide (Fe2O3).

[0117] [Dispersant]

[0118] The carburizing coating agent of this embodiment may also be free of dispersant. When it is contained, the amount of water used to disperse the glass frit and carbon powder can be reduced, resulting in improved adhesion of the carburizing coating agent to the steel surface.

[0119] The dispersant is, for example, one or more selected from the group consisting of inorganic salts such as sodium tripolyphosphate, sodium hexametaphosphate, sodium hyperpolyphosphate, acidic sodium hexametaphosphate, sodium borate, sodium carbonate, polymetaphosphate, sodium citrate, sodium tartrate, polyacrylic acid, sodium polyacrylate, sodium sulfonate, polycarboxylate, β-naphthalenesulfonate, melamine sulfonate, and naphthalenesulfonic acid. In the carburizing coating agent, the total content of the dispersant is preferably less than 4.5 parts by weight relative to 100 parts by weight of the glass frit.

[0120] [Preferred softening point for glass frit]

[0121] The preferred softening point of the glass frit contained in the carburizing coating agent is 600°C or higher. The softening point of the glass frit is determined by its composition. If the glass frit composition of this embodiment is used, the softening point is 600°C or higher. If the softening point of the glass frit is 600°C or higher, the carburizing coating agent wets and spreads on the steel surface in the high-temperature region of 950–1300°C, and sufficiently covers the steel surface. As a result, it promotes the formation of a carburized layer on the steel surface. Therefore, the preferred softening point of the glass frit is 600°C or higher.

[0122] The preferred lower limit for the softening point of the glass frit is 630°C, and the preferred lower limit is 650°C.

[0123] There is no particular upper limit to the softening point of the glass material, but it is preferably below 900°C, and more preferably 890°C.

[0124] [Method for determining softening point]

[0125] The softening point of the carburizing coating agent was determined using a thermogravimetric-differential thermal analysis (TG-DTA) apparatus. Specifically, 10 mg of the carburizing coating agent was placed in the sample holder of the TG-DTA. The carburizing coating agent was heated from room temperature to 1300°C at a heating rate of 10°C / min. The heating atmosphere was Ar. The differential thermal analysis was measured at this point, and the fourth inflection point of the DTA (differential thermal analysis) curve was taken as the softening point of the carburizing coating agent.

[0126] [Manufacturing method of carburizing coating agent]

[0127] The carburizing coating agent of this embodiment is manufactured, for example, by the following method.

[0128] Specifically, the raw materials for the glass frit with the above chemical composition are prepared. The prepared components are mixed. The mixed components are melted. The molten components are rapidly cooled in water or air to vitrify. The melting temperature is, for example, 1400–1600°C. The rapidly cooled vitrified intermediate is pulverized. Pulverization is performed, for example, using a ball mill. Through the above steps, the glass frit is manufactured. It should be noted that the softening point of the glass frit can be adjusted to, for example, above 600°C by adjusting the components before mixing. Water, for example, is added to the prepared glass frit to produce a slurry-like carburizing coating agent.

[0129] Carbon powder is further mixed into the slurry-like carburizing coating agent. At this point, the amount of carbon powder is adjusted so that the carbon powder ratio to RA is 0.10 to 0.49. Furthermore, a suspending agent and / or a dispersant are added to the slurry-like carburizing coating agent as needed. Through the above steps, the carburizing coating agent is manufactured.

[0130] [Manufacturing method of steel using carburizing coating agent]

[0131] The steel manufacturing method of this embodiment includes the following steps: a step of applying a carburizing agent to the surface of the steel (coating step); and a step of heating the steel coated with the carburizing agent at 950 to 1300°C (heating step). Each step will be described below.

[0132] [Coating Process]

[0133] In the coating process, firstly, the carburizing coating agent of this embodiment, manufactured as described in the above-described [method for manufacturing carburizing coating agent], is prepared. The prepared slurry-like carburizing coating agent is then applied to the steel surface (upper surface, lower surface, and side surface) before heating. For example, the carburizing coating agent is applied to the steel surface at room temperature.

[0134] There are no particular limitations on the application method of the carburizing agent. The operator can apply the carburizing agent to the surface of the steel using a brush. Alternatively, the carburizing agent can be applied to the steel surface by spraying or other methods. The steel can also be immersed in a bath containing the carburizing agent (so-called "immersion coating"). Through these application methods, a slurry-like carburizing agent is applied to the surface of the steel. Alternatively, after applying the slurry-like carburizing agent to the surface of the steel, the carburizing agent can be dried before heating the steel in the aforementioned temperature range.

[0135] There is no particular limitation on the amount of carburizing coating agent applied to the steel surface. For example, the application amount of a slurry-like carburizing coating agent to the steel surface is 0.1–0.3 g / cm³. 2 .

[0136] [Steel as the object]

[0137] In the manufacturing method of this embodiment, the type of steel used is not particularly limited. Preferably, the steel used is carbon steel. Here, carbon steel refers to carbon steel for mechanical structures as specified in JIS G 4051:2023 and carbon steel pipes for general mechanical structures as specified in JIS G 3478:2021. When these steels are heated at high temperatures in a furnace with an oxidizing atmosphere, an oxide scale composed of Fe oxides is formed on the surface of the steel.

[0138] [Heating Process]

[0139] The steel coated with a carburizing agent is heated (heating process). In the heating process, the steel coated with the carburizing agent is heated in a temperature range of 950–1300°C. The heating time is not particularly limited. The preferred upper limit of the heating temperature is 1250°C, more preferably 1200°C. The heating time is, for example, 1.0–8.0 hours. The preferred upper limit of the heating time is 5.0 hours, more preferably 2.5 hours.

[0140] The carburizing coating agent of this embodiment contains glass frit and carbon powder having the above-described composition, and the carbon powder ratio RA is 0.10 to 0.49. When the steel is maintained at a temperature range of 950 to 1300°C in a heat treatment furnace under an oxidizing atmosphere, the carburizing coating agent of this embodiment wets and spreads on the steel surface, forming a CO gas dispersion inhibition film that fully covers the steel surface. This CO gas dispersion inhibition film allows oxygen from the outside to permeate to some extent. Between the CO gas dispersion inhibition film and the steel surface, oxygen permeating from the outside combines with the carbon in the CO gas dispersion inhibition film to generate CO gas. The CO gas dispersion inhibition film allows oxygen to permeate but inhibits the permeation of CO gas. Therefore, CO gas remains between the CO gas dispersion inhibition film and the steel surface. As a result, the steel surface is sufficiently carburized.

[0141] Example

[0142] The effects of the carburizing coating agent according to the embodiments of the present disclosure will be further illustrated in detail below through examples. The conditions in the following examples are one example of conditions adopted to confirm the feasibility and effectiveness of the carburizing coating agent according to the embodiments of the present disclosure. Therefore, the carburizing coating agent according to the embodiments of the present disclosure is not limited to this one example of conditions.

[0143] In this embodiment, a carburizing coating agent is prepared by mixing various glass frits and graphite powders with different compositions in various mass ratios. Steel coated with the carburizing coating agent is heated at a high temperature, and the change in carbon concentration on the surface of the steel before and after heating is investigated. This embodiment will be described in detail below.

[0144] Glass frits (glass frit symbols A to O) as shown in Table 1 were prepared. The composition of the glass frits in Table 1 was determined using the method described in the [Method for Composition Analysis of Glass Frits] above. It should be noted that glass frit symbol F cannot be manufactured because the SiO2 content exceeds the upper limit, making it impossible to melt the mixed components. Similarly, glass frit symbol H cannot be manufactured because the Al2O3 content exceeds the upper limit, making it impossible to melt the mixed components. It should be noted that the impurity in glass frit symbol A is Fe2O3.

[0145] [Table 1]

[0146]

[0147] The glass frit, water, and suspending agent of the glass frit symbols in Table 1 were mixed to prepare the carburizing coating agents for each test number in Table 2. Each carburizing coating agent was prepared by mixing 70 parts by mass of water, 6 parts by mass of frog-eye clay, and 5 parts by mass of bentonite with 100 parts by mass of glass frit.

[0148] [Table 2]

[0149]

[0150] As plate-shaped test pieces, carbon steel equivalent to JIS standard S45C was used. The dimensions of the plate-shaped test pieces were 10 mm thick, 20 mm long, and 20 mm wide. The carbon content of each plate-shaped test piece was 0.45% by mass. Therefore, the carbon concentration [C] on the surface (steel surface) of each plate-shaped test piece was determined. B It is 0.45% by mass.

[0151] The above-mentioned carburizing coating agent was applied to the upper surface (20×20 mm) of the plate-shaped test piece using a brush and then dried. The coating amount for each test number is shown in Table 2. The coating amount was determined by the following method: The mass of the plate-shaped test piece before coating and the overall mass of the test piece after applying the carburizing coating agent were measured separately, and the coating amount of the carburizing coating agent was calculated from the difference between the two.

[0152] Plate-shaped test pieces coated with carburizing agent were heated for 1.0 hour at the heating temperatures (900–1300 °C) recorded in Table 2. The atmosphere simulated LNG combustion. Specifically, the atmosphere gas composition was adjusted to be 2–3% O2, 8–10% CO2, 15–20% H2O, with the balance being N2.

[0153] The C concentration (mass %) on the surface (steel surface) of a heated plate-shaped test piece was determined by the following method.

[0154] A cross-section perpendicular to the length direction (parallel to the width and thickness directions) at the center of the plate-shaped test piece was used as the observation surface. Five measurement points, spaced 1 mm apart in the width direction, were determined on the surface of the plate-shaped test piece at the center of the width direction within the observation surface. These five measurement points were positioned such that the middle measurement point in the row was located at the center of the width direction of the observation surface. Line analysis using an electron probe microanalyzer (EPMA) was performed along a 2000 μm thickness segment from this measurement point. In the EPMA-based line analysis, the accelerating voltage was 15 kV, the irradiation current was 500 nA, the electron beam diameter was 3 μm, and the measurement spacing was 4 μm. The above line analysis was performed on the five measurement segments of the observation surface. At each measurement segment, Fe, O, and C-based spectra were obtained from the surface of the plate-shaped test piece to a thickness of 2000 μm.

[0155] Figure 1 This is a schematic diagram showing the Fe, O, and C-based spectra obtained via EPMA. Figure 1 In the diagram, the horizontal axis represents the distance (μm) from the measurement point on the plate-shaped test piece, i.e., the surface along the thickness direction. Figure 1 In the graph, the vertical axis of the spectra of Fe, O, and C represents their concentrations as a percentage of mass. (Refer to...) Figure 1 The Fe concentration varies from the surface to the thickness D. C Up to this point, there is a downward-convex peak, and the concentration of O decreases from the surface to the thickness D. C Up to this point, there is a convex peak. That is, it can be determined that these Fe and O-based materials have a thickness up to D. C The peaks observed up to the thickness D are caused by the carburizing coating and oxide film adhering to the surface of the plate-shaped test piece. Therefore, the peaks up to the thickness D are obtained by EPMA based on the Fe, O, and C spectra. C Except for the peaks mentioned above. It should be noted that the thickness D... C Defined as follows.

[0156] In the O-based spectrum, the concentration of O at which the upward peak caused by the carburizing agent and oxide coating decreases and reaches its minimum is defined as [O]. S Here, the minimum point is the point where the concentration of O changes from decreasing to increasing; it refers to the location where the first differential is zero. The distance along the thickness direction from the surface to the minimum point is defined as the thickness D. C Then, determine the thickness D. C At a position of 500 μm in the thickness direction, i.e., thickness D R Determine the thickness D in the spectrum based on carbon (C). C To thickness D R The arithmetic mean of the C concentrations up to this point. It should be noted that, referring to... Figure 1 The extremely low and sharp C concentration peaks, such as peak LP, are attributed to impurities. Therefore, peak LP is based on the thickness D... C To thickness D R The C concentration in the spectrum up to this point is excluded from the arithmetic mean. Peak LP is determined using the following method.

[0157] Let the concentration C at the moment when the peak decay begins be set as concentration C[C]. S Let the concentration C at the moment when the peak decay ends be set as concentration C[C]. M Peaks with a peak attenuation rate (%) of 30% or higher, calculated using the following formula, are identified as peaks LP and excluded from the arithmetic mean of C concentrations.

[0158] Peak attenuation rate = ([C]) S -[C] M ) / [C] S ×100

[0159] The thickness D is obtained from 5 measurement lines using EPMA. C To thickness D R The arithmetic mean of the C concentrations up to this point is defined as the C concentration [C] on the surface of the heated steel. A (quality%).

[0160] Based on the obtained C concentration [C] A The carbon concentration [C] on the surface (steel surface) of the plate-shaped test piece before heating. B The concentration ratio ΔC can be calculated using the following formula.

[0161] ΔC = C concentration [C] A / C concentration [C] B

[0162] The obtained C concentration ratio ΔC is shown in the "ΔC" column of Table 2.

[0163] [Experimental Results]

[0164] Referring to Tables 1 and 2, the carburizing coating agents of test numbers 1 to 7 meet the range of each component of the glass charge, with a carbon powder ratio RA of 0.10 to 0.49. Therefore, for the carburizing coating agents of these embodiments, the C concentration ratio ΔC is 1.30 or higher, enabling carburizing treatment in a heat treatment furnace using an oxidizing atmosphere.

[0165] On the other hand, for the carburizing coating agents in tests 8 and 9, the carbon powder ratio RA was less than 0.10. Therefore, the C concentration ratio ΔC was less than 1.30, making carburizing treatment in a heat treatment furnace using an oxidizing atmosphere impossible.

[0166] For the carburizing coating agent in test number 10, the carbon powder ratio RA exceeds 0.49. Therefore, the C concentration ratio ΔC is less than 1.30, making carburizing treatment in a heat treatment furnace using an oxidizing atmosphere impossible.

[0167] For the carburizing agent in test number 11, the heating temperature of the plate-shaped test piece after applying the carburizing agent was below 950°C. Therefore, the C concentration ratio ΔC was less than 1.30, making carburizing treatment in a heat treatment furnace using an oxidizing atmosphere impossible.

[0168] For the carburizing agent in test number 12, the SiO2 content in each component of the glass frit is below the lower limit. Therefore, the C concentration ratio ΔC is less than 1.30, making carburizing treatment in a heat treatment furnace using an oxidizing atmosphere impossible.

[0169] For the carburizing agent in test number 13, the Al2O3 content in the glass frit was below the lower limit. Therefore, the C concentration ratio ΔC was less than 1.30, making carburizing treatment in a heat treatment furnace using an oxidizing atmosphere impossible.

[0170] For the carburizing agent in test number 14, the B2O3 content in each component of the glass frit exceeded the upper limit. Therefore, the C concentration ratio ΔC was less than 1.30, making carburizing treatment in a heat treatment furnace using an oxidizing atmosphere impossible.

[0171] For the carburizing agents in tests 15 and 16, the K₂O content in each component of the glass frit exceeded the upper limit. Therefore, the C concentration ratio ΔC was less than 1.30, making carburizing treatment in a heat treatment furnace using an oxidizing atmosphere impossible.

[0172] For the carburizing agents in tests 17 and 18, the CaO content in each component of the glass frit exceeded the upper limit. Therefore, the C concentration ratio ΔC was less than 1.30, making carburizing treatment in a heat treatment furnace using an oxidizing atmosphere impossible.

[0173] For the carburizing agents in tests 19 and 20, the MgO content in each component of the glass frit exceeded the upper limit. Therefore, the C concentration ratio ΔC was less than 1.30, making carburizing treatment in a heat treatment furnace using an oxidizing atmosphere impossible.

[0174] The embodiments of this disclosure have been described above. However, the above embodiments are merely illustrative examples for implementing this disclosure. Therefore, this disclosure is not limited to the above embodiments, and appropriate modifications can be made to the above embodiments without departing from its spirit.

Claims

1. A carburizing coating agent, comprising: Glass material; and Carbon powder, The glass frit contains, by mass percent when converted to oxides: SiO2: 20.0%~40.0% Al2O3: 10.0–30.0% B2O3: 9.0–40.0% Na2O: 0~30.0% K2O: 0-5.0% CaO: 0–7.0%, and MgO: 0–5.0%, The mass ratio of the carbon powder in the carburizing coating agent to the mass of the glass frit is 0.10 to 0.49, wherein the mass of the carbon powder and the mass of the glass frit are in grams.

2. A method for manufacturing steel, comprising the following steps: The process of applying the carburizing coating agent of claim 1 to the surface of steel; and The process of heating the steel coated with the carburizing agent at 950-1300°C.

Citation Information

Patent Citations

  • Coating type carburizing composition, and carburizing method using it

    JP2000119838A

  • Carburizing treatment method

    JP2001115249A

  • Surface treatment agent of steel product, and surface treatment method of steel product

    JP2016223011A